7 days in Entebbe [videorecording (DVD)] - Pike, Rosamund, 1979-; Marsan, Eddie; Brühl, Daniel, 1978- (Universal Pictures Home Entertainment, 2018)
Israeli soldiers embark on a mission to rescue more than 240 hostages from an airport in Entebbe, Uganda, in the summer of 1976.